Intelligent and adaptive educational-learning systems achievements and trends - Peña-Ayala, Alejandro (Smart innovation, systems and technologies, 2013)
The Smart Innovation, Systems and Technologies book series encompasses the topics of knowledge, intelligence, innovation and sustainability. The aim of the series is to make available a platform for the publication of books on all aspects of single and multi-disciplinary research on these themes in order to make the latest results available in a readily-accessible form.  This book is devoted to the “Intelligent and Adaptive Educational-Learning Systems”. It privileges works that highlight key achievements and outline trends to inspire future research.  After a rigorous revision process twenty manuscripts were accepted and organized into four parts as follows: ·     Modeling: The first part embraces five chapters oriented to: 1) shape the affective behavior; 2) depict the adaptive learning curriculum; 3) predict learning achievements; 4) mine learner models to outcome optimized and adaptive e-learning objects; 5) classify learning preferences of learners. ·     Content: The second part encompasses five chapters aimed to: 6) provide adaptive guidance and personalized content; 7) adaptively select learning objects; 8) collaboratively generate learning objects; 9) automatic development of reusable adaptive content; 10) deploy intelligent tutoring systems as learning objects. ·     Virtuality: The third part holds four chapters dedicated to: 11) explain how Second Life was used to promote collaborative writing; 12) acquire knowledge within a smart home environment; 13) share experiences of adaptive training virtual systems; 14) reveal how an agent is used in a simulation-based tutoring system for learning the complex task of operating a robotic arm. ·     Applications: The fourth part owns six chapters concerned about: 15) an agent-based way to design scaffolding to prompt reflection; 16) the stimulation of self-regulated to learn higher order knowledge; 17) a web-mediated training system design architecture; 18) a decision making mo